The changing graduate labour market: Analysis using a new indicator of graduate jobs - Francis Green; Golo Henseke (IZA Journal of Labor Policy, 2016)
This paper examines differentiation in the recent evolving graduate labour market in Britain. Using a novel statistically derived indicator of graduate jobs, based on job skill requirements in three-digit occupations obtained from the British Skills and Employment Survey series, we analyse trends in the labour market between 1997/2001 and 2006/2012. The indicator performs better than other indicators in validation tests, could be applied flexibly in other contexts, and is available in the Additional file 1. We find that the massive influx of graduates into the labour force has been absorbed with no increase in overeducation. However, the returns to graduation have become more dispersed, with those at the upper quartile of the residual distribution increasing, while those at the lowest quartile have fallen. The wage gap between matched and overeducated graduates increased by 11 log points. Using the British Household Panel Study, we find that the persistence of overeducation status did not change but for non-employed male graduates moving into employment, the chances of entering a graduate job decreased.
Keywords: J21; J24; J3; 330; Higher education; Wages; Skills; Overeducation; Tertiary education